IMPLIKASI TEORI BELAJAR KONSTRUKTIVISME VYGORSKY TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Imelda Ch Pocerattu (TANGKOLEH PUTAI, 2023)
Constructivism theory is one of many learning theories that have been designed in the implementation of Christian Religious Education learning. Like behaviorism and cognitivism, constructivism can be applied in various learning activities in both the social and exact sciences. The purpose of this study is to describe the implications of Vygotsky's theory of constructivism in the implementation of the Christian Religious Education learning model, the urgency of constructivism theory in Christian Religious Education learning and the implications of constructivism in PAK learning. This research is a theoretical research with data acquisition through various articles in various journals, books, and other print media related to Vygotsky's theory of constructivism. The results of this study indicate that the implications of constructivism theory in the implementation of PAK learning are very appropriate. Students will be more enthusiastic if learning is more student focused.